Simple, concise, stereocontrolled synthesis of (8E,10Z)-pentadecadien-1-ol acetate - Chavan, Subhash P.; Kharul, Rajendra K.; Kamat, Subhash K.; Kalkote, Uttam R.; Kale, R. R. (Synthetic Communications, 2005)
A simple, concise, and stereocontrolled synthesis of (8E, 10Z)-pentadecadien-l -ol acetate involving a Cadiot-Chodkiewicz reaction as the key step is described.
Keywords: acetate; Acrobasis vaccini; Cadiot-Chodkiewicz reaction; diacetylene; Pheromone

Simplistic expedient and practical synthesis of (+/-)-alpha-lipoic acid - Chavan, Subhash P.; Shivsankar, K.; Pasupathy, K. (Synthesis-Stuttgart, 2005)
Synthesis of a-lipoic acid has been achieved by a simple sequence of reactions. The synthesis highlights the use of alpha-chloroesters in a Reformatsky reaction. The intermediate keto acid is an intermediate from which both isomers of lipoic acid can be prepared.
Keywords: alpha-chloroesters; alpha-lipoic acid; Ozonolysis; Reformatsky reaction

Stereoselective synthesis of (-)-microcarpalide - Chavan, Subhash P.; Praveen, C. (Tetrahedron Letters, 2005)
A highly convergent and efficient synthesis of (-)-microcarpalide, a 10-membered lactone displaying remarkable microfilament disrupting activity is described. Ring-closing metathesis and Sharpless asymmetric dihydroxylations are the key steps. Our strategy highlights the application of novel hydroxy lactone precursors for the stereoselective synthesis of (-)-microcarpalide. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: 4-diol; cis-2-butene-1; Claisen ortho ester rearrangement; microcarpalide; Ring-closing metathesis; sharpless asymmetric dihydroxylation

Synthesis of (+)-camptothecin - Chavan, Subhash P.; Venkatraman, M. S. (Arkivoc, 2005)
A synthesis of optically pure camptothecin was achieved in 4 steps from previously reported aldehyde employing Sharpless asymmetric dihydroxylation as the key step.
Keywords: Anticancer; camptothecin; sharpless asymmetric dihydroxylation

Short and efficient synthesis of rubrolide E - Chavan, Subhash P.; Pathak, Ashok B.; Pandey, Ankur; Kalkote, Uttam R. (Synthetic Communications, 2007)
Short and efficient synthesis of rubrolide E from commercially available 4-methoxyacetophenone, employing ring-closing metathesis, Knoevenagel condensation, and Reformatsky reactions, are the key steps are described.
Keywords: antibiotics; antitumor; Epoxide; Natural products; Total synthesis

Short synthesis of (2S,3S)-3-hydroxypipecolic acid - Chavan, Subhash P.; Harale, Kishor R.; Pawar, Kailash P. (Tetrahedron Letters, 2013)
A convenient synthesis of (2S,3S)-3-hydroxypipecolic acid starting from cheap and abundant L-(+)-tartaric acid has been achieved. The strategy employs selective ester reduction and reductive lactamization as key steps. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Reductive lactamization; Selective deprotection; Wittig reaction

Simple synthesis of the novel antihistaminic drug olopatadine hydrochloride - Chavan, Subhash P.; Lasonkar, Pradeep B. (Synthesis-Stuttgart, 2013)
A new alternative route for the synthesis of olopatadine is described. The present strategy involves a Lewis acid mediated ring opening of a cyclic ether to introduce 3-(dimethylamino)propylidene group as the side chain.
Keywords: antihistaminic drugs; chelates; Lewis acids; spiro compounds; zinc

Short enantioselective total synthesis of (R)- and (S)-pipecolic acid - Chavan, Subhash P.; Khairnar, Lalit B.; Chavan, Prakash N.; Kalbhor, Dinesh B. (Tetrahedron-Asymmetry, 2014)
A convenient and practical total synthesis of (R)- and (S)-pipecolic acid has been achieved by utilizing chiral cis-aziridine-2-carboxylate as the common synthetic precursor. The synthesis involves regioselective reductive cleavage of the aziridine ring and Wittig olefination as key reactions. (C) 2014 Elsevier Ltd. All rights reserved.

Stereospecific synthetic approach towards tamiflu using the ramberg-backlund reaction from cysteine hydrochloride - Chavan, Subhash P.; Chavan, Prakash N.; Gonnade, Rajesh G. (RSC Advances, 2014)
The stereospecific formal synthesis of Tamiflu from L-cysteine hydrochloride as the chiral source is described. The notable feature of the present strategy is the Ramberg-Backlund reaction and Sharpless-Reich protocol as the key chemical transformations to access the cyclohexene skeleton of Tamiflu.

Synthesis of 3-ethyl-4-metyl-1h,5-dihydro-2h-pyrrol-2-one by novel palladium(ii)-catalyzed cyclization and ring-closing metathesis - Chavan, Subhash P.; Pathak, Ashok B.; Pawar, Kailash P. (Synthesis-Stuttgart, 2015)
Synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one is described starting from commercially available allylamine and 4-methoxybenzylamine employing palladium-catalyzed cyclization or ring-closing metathesis as the key steps.
Keywords: antidiabetic; cyclization; glimepiride; lactams; metabolite; pyrrolinone; Ring-closing metathesis

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocycl- yl-2,6-dicyanoanilines - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Dipak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2017)
Synthesis of 3,4,5-triheterocyclyl-2,6-dicyanoanilines, starting from heterocyclic aldehydes and 1,2-diheterocycle-substituted ethanones, is described. 2,6-Dicyanoanilines with one or two heterocyclic substituents have also been synthesized. It was found that some of these molecules have selective cell-staining properties useful for cell imaging applications. The compounds 1g, 10f and 11 were found to stain cytoplasm of the cells in contact but not the nucleus while the compound 12 showed affinity to apoptotic cells resulting in blue fluorescence. The cell imaging results with compound 12 were similar to Annexin V-FITC, a known reagent containing recombinant Annexin V conjugated to green-fluorescent FITC dye, used for detection of apoptotic cells. These compounds were found to be non-cytotoxic and have potential application as cell imaging agents.

Synthesis of 3-azidopiperidine skeleton employing ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether: total synthesis of d-2 receptor agonist (+/-)-quinagolide - Chavan, Subhash P.; Kadam, Appasaheb L.; Lasonkar, Pradeep B.; Gonnade, Rajesh G. (Organic letters, 2018)
The total synthesis of (+/-)-quinagolide, which is a D-2 receptor agonist, was accomplished via a ceric ammonium nitrate (CAN)-mediated regioselective azidoalkoxylation of enol ether route. Key features of the synthesis include Claisen rearrangement, PPTS (pyridinium p-toluene-sulfonate)-catalyzed one-pot acetal deprotection, followed by a diastereoselective Henry reaction, which enables construction of the required trans ring junction and CAN-mediated regioselective azidoalkoxylation of enol ether. The PPTS-catalyzed intramolecular diastereoselective Henry reaction to fix three contiguous stereocenters on tetrahydronaphthalene and the first-of-its-kind synthesis of the 3-azidopiperidine skeleton, using a CAN -mediated regioselective azidoalkoxylation of enol ether, are important findings of the present work.

Scalable synthesis of 3-Ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one: an important building block of the antidiabetic drug glimepiride - Chavan, Subhash P.; Pawar, Ambaji A.; Patil, Niteen B.; Kadam, Appasaheb L.; Shinde, Shrikrishna S. (Synthesis-Stuttgart, 2020)
A four-step, practical, and easily scalable synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one, an important building block of the antidiabetic drug glimepiride, has been accomplished. Key features are the synthesis of 3-methyl-4-hydroxy-2-butenolide in water and triflic acid mediated N-benzyl lactam N-deprotection. The main advantages of this process are the scalable synthetic route and decreased number of reaction steps, which paves the way for the industrial-scale synthesis of 3-ethyl-4-methyl-1,5-dihydro-2H-pyrrol-2-one.
Keywords: antidiabetic drug; Butenolide; glimepiride; lactams; scalable synthesis

Synthesis and cell imaging applications of fluorescent mono/di/tri-heterocyclyl-2,6-dicyanoanilines (vol 27, pg 979, 2017) - Pisal, Mahesh M.; Annadate, Ritesh A.; Athalye, Meghana C.; Kumar, Deepak; Chavan, Subhash P.; Sarkar, Dhiman; Borate, Hanumant B. (Bioorganic & Medicinal Chemistry Letters, 2021)